EFFECT OF SEASONAL ON NUTRIENT LOAD INPUT THE INNER AMBON BAY - Pello, F.S.; Adiwilaga, E.M.; Huliselan, N.V.; Damar, A. (Bumi Lestari; Vol 14 No 1 (2014))
Input nutrients into the Inner Ambon Bay very influenced by season. Activity in the bay and input nutrients from land and  outer Ambon Bay as well as the influence of upwelling in  Banda sea could increase eutrophication in the bay. This study aimed to analyze the influence of freshwater and  the exchange of sea water to the concentration of nutrients in  Inner Ambon Bay. The study was conducted from June 2011 to May 2012. Average content of nitrate in East season (0.04 to 2.36 µM (0.57±0.78), Transition Season II 0.05 to 2.20 µM (0.36±0.67); and Transition Season I0.09 to 1.66 µM (0.59±0.47) are higher while the West season 0.05-0.10µM (0.06±0.02) is lower than the water quality standard for marine biota. Average value of phosphate in the four seasons is higher than the sea water quality standard, while enter nitrate and phosphates from Outer Ambon Bay in the East Season is larger than from river. Temporally and spatially condition of Inner Ambon Bay are oligotrophic and mesotrophic. Flushing time in Inner Ambon Bay is 14 days.
Keywords: Input nutrients into the Inner Ambon Bay very influenced by season. Activity in the bay and input nutrients from land and outer Ambon Bay as well as the influence of upwelling in Banda sea could increase eutrophication in the bay. This study aimed to an